The Main Trends of Development of the Radical Far-Right in the EU Member Countries (The Case of the 2010s) - Lortkiphanidze, Levan (Politics / პოლიტიკა, 2018)
The paper discusses the concept and the criteria of radical right wing parties, according to which a political organization can be categorized. Moreover, the study examines the history and the causes of origin and rise of radical right-wing parties. The article outlines different subgroups belonging to the radical right-wing parties. The author attempts to differentiate such terms as right-wing populism, right wing extremism, right wing nationalism, and Euroscepticism. Additionally, the parallels are drawn between the examples of transformation of the European and the Georgian party systems.